The oldest terrestrial mineral record: Thirty years of research on Hadean zircon from Jack Hills, Western Australia - Cavosie, Aaron; Valley, J.; Wilde, S. (Elsevier, 2018)
Investigations conducted over the last three decades on Hadean zircon from the Jack Hills, Western Australia, have demonstrated unequivocally that the clastic metasedimentary rocks there contain the most diverse repository of preserved Hadean material on Earth. Detailed study of rare detrital grains as old as 4400 Ma provides the only direct record of geological processes active on Earth shortly after its formation. Research on the Jack Hills population has focused on many different aspects of zircon, and a consensus exists that despite their long and complex histories, most non-metamict grains preserve evidence of an igneous origin. However, the nature and cause of the early magmatism is debated. Igneous crystallization ages up to 4400 Ma provide unequivocal evidence for the former existence of crust ca. 400 million years earlier than the oldest intact rocks. Different geochemical tracers record derivation of parental magmas from primordial mafic crust (Hf), followed by widespread magmatic recycling of rocks altered at low temperature by liquid water (O, Li). The aqueous alteration of Earth’s surface, as recorded by Hadean zircon (O), reflects global cooling, and may record the end of “Hadean” (Hell-like) conditions. Trace element concentrations in Hadean grains (REE, Ti, Al, P, Y) are mostly similar to those in younger zircon from metaluminous granitoid generated at low magmatic temperatures, indicating consistent petrogenetic conditions. Ongoing areas of research on the Jack Hills zircon suite are focused on constraining the environment(s) of the early magmatism, as well as the connection, if any, of Hadean zircon to fundamental stages of planetary evolution, such as early meteorite bombardment, establishment of habitable surface conditions, and the onset of tectonic processes.